Multilateral teaching in physical education improves resilience and self-efficacy in adolescents and could help reduce bullying behaviors - Greco Gianpiero (Sciendo, 2021)
Youth with higher levels of resilience and self-efficacy are less likely to engage in aggressive behaviors or be victims of bullying. Previous anti-bullying approaches have often achieved no reduction in bullying behavior. Thus, the aim of this study was to examine the effect of 12 weeks of extracurricular multilateral teaching on the risk for students (aged 14-16 years) to be involved in bullying. Sixty male students were allocated to an experimental group (n = 30) that performed psychoeducational activities combined with physical exercise training and team games (90 min, 2d · week-1) or a control group (n = 30). Before and after the intervention, we used the Child and Youth Resilience Measure (CYRM-28) to assess individual capacities and resources, relationship with primary caregiver, contextual factors, and total resilience; and the Self-Efficacy Questionnaire for Children (SEQ-C) to measure academic, social, emotional, and total self-efficacy. Four participants from the experimental group withdrew. Significant improvements of crucial relevance were found for the resilience and self-efficacy scales (p < 0.05) in the experimental group. We found that multilateral teaching may improve resilience and self-efficacy in adolescents and make them less likely to engage in aggressive behavior or be bullied. Multilateral teaching should be considered an effective alternative to the anti-bullying approach, highlighting the crucial role of physical education teachers in the promotion of proactive educational strategies to reduce bullying behaviors.